2008
DOI: 10.1002/mame.200700194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Correlation between Mechanical Non‐Linearity in LAOS Flow and Capillary Flow Instabilities for Linear and Branched Commercial Polyethylenes

Abstract: An experimental correlation between the non‐linear behaviour of commercial polyethylene melts in LAOS flow, and the pressure fluctuations associated with melt flow instabilities developed in capillary rheometry are presented. Polyethylene melts with enhanced non‐linear behaviour under LAOS conditions present larger pressure fluctuations during capillary extrusion, and consequently, larger surface distortions on the extrudate. The combination of both methods can be a tool to predict the development of melt flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
6
32
0
Order By: Relevance
“…To the best of our knowledge, this set‐up combined with our mathematical framework is unique and can obtain direct experimental evidence of pressure oscillations inside a die associated with a sharkskin phenomenon 10, 33. Other techniques are not able to detect this kind of fast and small instability since the detection of a relative pressure oscillation of around 0.05% with respect to the main value is needed in combination with a high acquisition rate, of around 3 × 10 4 experimental points per second in our case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this set‐up combined with our mathematical framework is unique and can obtain direct experimental evidence of pressure oscillations inside a die associated with a sharkskin phenomenon 10, 33. Other techniques are not able to detect this kind of fast and small instability since the detection of a relative pressure oscillation of around 0.05% with respect to the main value is needed in combination with a high acquisition rate, of around 3 × 10 4 experimental points per second in our case.…”
Section: Resultsmentioning
confidence: 99%
“…Upon increasing the shear rate, some polymers show spurt instability (also named stick‐slip, and is different to the sharkskin phenomenon) characterized by large pressure oscillations where the extrudate alternates between rough and smooth sections. In general, linear polyethylenes and polymers with high molecular weights and high polydispersities can present this instability 9, 10. Finally, at high shear rates, other instabilities appear that are associated with bulk phenomena in the entrance of the die (e.g., helicoidal defects, gross melt‐fractures, spirals, etc).…”
Section: Introductionmentioning
confidence: 99%
“…The slope is also independent of MW, MWD, and the measurement conditions. [162,[167][168][169][170][171][172] The rheological properties discussed above are conventionally used for LCB characterization, but many other rheological parameters such as the first normal stress coefficient (ψ1) enhancement, [100] the critical tensile stress (σ c ) for the onset of gross melt fracture, [173] the sharkskin periodicity [174,175] and the stick-slip flow [176] in capillary extrusion experiments and so on can be also used.…”
Section: Characteristic Relaxation Time and Damping Functionmentioning
confidence: 99%
“…The precise origins of sharkskin instability are still unclear . Although many publications suggest that its origin is related to phenomenon at the die exit, Palza and Filipe showed that it can be measured throughout the whole die by using an in situ measurement technique based on piezoelectric pressure transducers. The stick‐slip instability, referred to as just stick‐slip henceforth, is characterized by alternating smooth and rough regions at the extrudates surface.…”
Section: Introductionmentioning
confidence: 99%
“…The optical method proposed in this article is not designed to replace the sharkskin procedure . That method remains the best approach for understanding instabilities in highly controlled laboratory experiments where the sharkskin option is available.…”
Section: Introductionmentioning
confidence: 99%